PKM Pendampingan dan Pelatihan Microsoft Office untuk Meningkatkan Keterampilan Santri Pesantren Nurul Hidayah - Sudriyanto Sudriyanto; Sukma Agung Adi Luwih; Syamsul Arifin; Wahyu Pratama Mukti; Wakiludinil Hasan (GUYUB: Journal of Community Engagement, 2022)
The development of technology has helped a lot of human work. One of the things that we can enjoy from these technological developments include Microsoft Word, Microsoft Excel and power points. Microsoft Word, functions as a word processing software includes creating, editing, and formatting documents. The students have not been able to operate Microsoft word, Excel and Power Point because they are not taught at school, the high cost of computer courses among students. One of them is to train the ability to use a word processing application, namely Microsoft Word. Community service activities are emphasized in the form of training on how to apply Microsoft Office for students of the Nurul Hidayah Islamic Boarding School. It is hoped that with this training, students can know more about the basic techniques of using Microsoft Office by utilizing Microsoft Word, Microsoft Excel, Microsoft Power Point. The results of the service activities carried out provide experience and skills for students in using Microsoft Office. Thus, the implementation of community service activities at the Nurul Hidayah Islamic Boarding School Foundation Using Microsoft Office provides significant benefits for improving the skills of students in utilizing information technology and computers. The students were very enthusiastic about participating in further training activities. The students already understand and can run Microsoft Office applications.